PENGARUH WORKING CAPITAL TURNOVER (WCT), CURRENT RATIO (CR), DAN TOTAL ASSETS TURNOVER (TATO) TERHADAP PROFITABILITAS - Melia Trie Utami; Gusganda Suria Manda (Universitas Bina Sarana Informatika, 2021)
The purpose of this study was to examine and analyze the effect of Working Capital Turnover (WCT), Current Ratio (CR), and Total Assets Turnover (TATO) on Profitability with the Return On Assets (ROA) proxy on cigarette sub sector companies listed on the Indonesia Stock Exchange (IDX) quarterly in 2014-2019, both partially and simultaneously. The research method used is descriptive verification with quantitative approaches. The sample in this study used purposive sampling. The statistical method used is the method of multiple linear regression analysis. The results showed that the Working Capital Turnover (WCT), Current Ratio (CR), and Total Assets Turnover (TATO) simultaneously had a significant effect on the Return on Assets (ROA) profitability. Partially Working Capital Turnover (WCT) has a significant negative effect on Return on Assets (ROA) profitability, Current Ratio (CR) has no effect on Return on Assets (ROA) Profitability, and Total Assets Turnover (TATO) has a significant positive effect on Return on Profitability Assets (ROA). The coefficient of determination obtained by 0.429 means that only 42.9% Profitability Return on Assets (ROA) is influenced by Working Capital Turnover (WCT), Current Ratio (CR), and Total Assets Turnover (TATO) and the rest 57.1 % is influenced by other variables.